Halal Tourism and Muslim Family Well-Being: A Maqāṣid Based Socio-Legal Analysis In Indonesia - JM Muslimin; Umar Al Haddad; Ahmad Yani; M. Firdaus; Siebel N. Mayuk (Mawaddah: Jurnal Hukum Keluarga Islam, 2026)
The rapid expansion of the halal economy has reshaped Muslim consumption patterns, particularly in the tourism sector. While existing studies emphasize halal tourism development, they largely overlook its socio-legal transformation and its role in shaping Muslim family well-being. This study fills the gap by integrating maqāṣid al-sharī‘ah with socio-legal and consumption theory to examine how Islamic tourism is reinterpreted within contemporary Muslim family life in Indonesia. This research employs a qualitative-dominant mixed-method approach with a sequential explanatory design, combining survey data and in-depth interviews with Muslim families in Bandung and Garut. The findings reveal a significant perceptual shift, with approximately 72% of respondents recognizing tourism as compatible with Islamic values when aligned with halal principles, and 68% considering it a primary component of family well-being. Tourism is increasingly understood as contributing to psychological relaxation, emotional bonding, and quality of life. Furthermore, the institutionalization of halal tourism through sharia-compliant services enhances its legitimacy and accessibility. Theoretically, this study demonstrates that tourism can be reinterpreted through the lens of maqāṣid al-sharī‘ah as a means of achieving holistic well-being, challenging the assumption that leisure consumption is normatively contested in Islam. Practically, it highlights the strategic role of Muslim families as value-driven consumers within the halal ecosystem. This study contributes to socio-legal and consumption scholarship by positioning halal tourism as a key driver of contemporary Muslim family well-being.